MODELLING OF ACOUSTIC EMISSION SIGNALS FOR THE CASE OF MATERIAL SURFACE LAYERS DISTRACTION IN THE PROCESS OF FRICTION - Filonenko, Sergey F.; Stakhova, Аngelika P.; Kositskaya, Tatiana M. (Proceedings of National Aviation University (archive), 2008)
The obtained data of the resulting acoustic signals emission at the prevailing mechanism of the material surface layer wear under friction have been considered. It has been shown that the form and parameters of the acoustic emission resulting signals depend on the time of the initiation of type-I or type-II secondary structures fracture (rotation velocity of friction pair), as well as the stressed-deformed state of the materials’ surface layers of friction pairs.